“Construction Grammar” and Academic Communication: A Cross-Linguistic Perspective - N. K. Riabtseva (Научный диалог)
The article studies special types of grammatical constructions characteristic to Russian academic style, and the ways of their translation into English, primarily when used in academic paper titles. In accordance with “Construction Grammar”, three types of actively used constructions are discussed, which are particularly “sensitive” to cross-linguistic context: (1) “ X na materiale / na primere / na osnovanii Y etc.,” (2) “ X v svete / skvoz’ prizmu / v zerkale / s tochki zreniya / v kontekste / v aspecte (and so on) Y ,” (3) “ X kak sredstvo / kak osnova / kak sposob / kak kluch (and so on) k Y .” It is shown that such grammatical constructions in contemporary academic style in Russian as well as the analogous ones in English reflect the dynamic character of language evolution, discourse and communication; are generated on the basis of “family resemblance” and prototype structures; belong to the compositional area of small syntax: they are used as integral discourse units; represent irregular, but frequently lexicalized phrases and non-standard grammatical structures; are idiomatic and “language-specific” and therefore their translation requires finding “quasiequivalents” and “quasisynonyms” in other languages.